Aktivitas Antibakteri Ekstrak Etanol Umbi Porang (Amorphophallus muelleri Blume) terhadap Propionibacterium acnes dan Staphylococcus epidermidis - Alfi Sapitri; Eva Diansari Marbun; Retnita Ernayani Lubis; Dian Arisetya (Herbal Medicine Journal, 2026)
Porang tubers, scientifically known as Amorphophallus muelleri Blume, have shown that they possess compounds like alkaloids, flavonoids, saponins, and tannins. Because of this, researchers are looking closely at porang tubers to see how they can fight bacterial growth. Among the bacteria being investigated are Propionibacterium acnes and Staphylococcus epidermidis, as scientists search for new treatments for skin infections. Aim of reserach to assess how effective the antibacterial properties are and to analyze how different levels of extract concentration affect the growth of Propionibacterium acnes and Staphylococcus epidermidis. The method used for testing involved a paper disc diffusion technique with extract concentrations of 5, 15, 25, 35, and 45%, as well as Clindamycin and 10% DMSO. The findings revealed that the ethanol extract from porang tubers displayed antibacterial effects at concentrations ranging from 5% to 45%, resulting in inhibition zones of 9. 65 mm to 13. 56 mm against Propionibacterium acnes. Additionally, it showed inhibition zones of 9. 95 mm to 16. 07 mm against Staphylococcus epidermidis in the same concentration range. According to the One Way Anova test, the results showed a significant difference indicating that varying concentrations of the ethanol extract from porang tubers greatly influenced the growth of both Propionibacterium acnes and Staphylococcus epidermidis. The ethanol extract of porang tubers begins to show antibacterial effects at a minimum concentration of 5% against both Propionibacterium acnes and Staphylococcus epidermidis, with observable differences in the average inhibition zones for each concentration tested.